Assessment of fire resistance of fireproof reinforced concrete structures - Kovalov, Andrii; Purdenko, Roman; Otrosh, Yurii; Tоmеnkо, Vitalii; Rashkevich, Nina; Shcholokov, Eduard; Pidhornyy, Mykola; Zolotova, Nina; Suprun, Oleg (Eastern-European Journal of Enterprise Technologies, 2022)
A finite-element model for the heat engineering calculation of fireproof reinforced concrete slab has been built, which is designed to assess the fire resistance of unprotected reinforced concrete structures. A feature of the model is the correct choice of types of heat transfer in the cavities of reinforced concrete ceilings. An algorithm that includes experimental and calculation procedures in determining the fire resistance of unprotected reinforced concrete structures has been applied. The initial, boundary conditions for the construction of the model were formulated; the thermophysical properties of materials were substantiated. Thermal calculation of fireproof multi-hollow reinforced concrete ceiling under conditions of fire was carried out. The adequacy of the developed finite-element model was checked. A satisfactory convergence of experimental and calculated temperatures with an accuracy of 10 % was established, which would suffice for the engineering calculations. The model built makes it possible to assess the fire resistance of unprotected reinforced concrete structures. Thus, there is reason to argue that the model constructed can partially or completely replace the experimental assessment of fire resistance, provided that the construction and setting of the model parameters are correct